The Development of Teachers’ Competences in Utilizing Augmented Reality-Based Media in Geometry Learning - Karlimah Karlimah; Asep Nuryadin; Lilis Susilawati; Benyamin Hartanto; Dindin Abdul Muiz Lidinillah; Muhammad Rijal Wahid Muharram; Sri Ariyani Desmawati; Irni Rachmawati Putri (LPPM Universitas Muhammadiyah Tasikmalaya, 2023)
This program aims to develop teachers’ competences in using and utilizing technology in the form of Augmented Reality (AR)-based media that can be used in geometry learning. This community service program is in the form of a training for elementary school teachers. This program is motivated by the results of a study which shows that of 257 teachers from 39 cities in Indonesia only 28% claimed to be familiar with AR-based media while 72% of teachers claimed not to know them, some of whom were teachers in Tasikmalaya City. Therefore, it is necessary to develop their competences so that they will know and be able to use AR-based media to adapt to the times. This training was carried out from the smallest scope, namely at an elementary school in Tasikmalaya City, SD Negeri Leuwianyar. The potential for using digital media in the school is quite high because the facilities are quite supportive. The problem was, teachers rarely used digital media, including the use of AR-based media. This training program was carried out by adapting the stages of the ADDIE model, namely Analyze, Design, Develop, Implement, and Evaluate. The results of the training showed that teachers strongly agreed that the training could develop their knowledge and encourage them to use AR-based digital media for learning.